Keanekaragaman Morfologis Ikan Uceng Nemacheilus fasciatus (Valenciennes, 1846) di Perairan Sungai Bogor, Temanggung dan Blitar - Yudha, Donan S.; Nafita, Hamdani F. (Jurnal Biologi Papua, 2024)
Uceng (Nemacheilus fasciatus) is relatively common fish in Indonesia. Characteristics of this are small and slender bodied with a line marking on the lateral part of its body. This species is distributed in Java and Sumatra. There are differences on geographical conditions such as water levels, water currents and the environment in each distribution area of this species. These differences may result in both morphology and genetic variations. This study aimed to determine morphological variations of uceng fish among populations from three different regions of rivers in Java, namely Cijeruk River in Bogor, Progo River in Temanggung and Lekso River in Blitar; and to compare its morphological variations between populations from those three difference regions. Methods used in this study was purposive sampling to collect samples, meristic and morphometric data acquisition, furthermore those data were analyzed using kruskall-Walis to test significant difference between each morphological characteristic, Mann-Whitney to determine the differences between populations and finally PCA data analysis to determine distributional patterns between each populations. Result showed significant morphological differences (p<0.005) between populations from three different rivers and there were differences in several morphometric and meristic characteristics between each populations.    Key words: morphological variations; Nemacheilus fasciatus; Bogor; Temanggung; Blitar